Studying the effect of temperature and treating time on some physical properties of carbon black - Younis, Samir B. (Iraqi Journal of Physics, 2012)
Samples prepared by using carbon black as a filler material and phenolic resin as a binder. The samples were pressed in a (3) cm diameter cylindrical die to (250)MPa and treated thermally within temperature range of (600-1000)oC for two and three hours. Physical properties tests were performed, like density, porosity, and X-ray tests. Moreover vicker microhardness and electric resistivity tests were done. From the results, it can be concluded that density was increased while porosity was decreased gradually with increasing temperature and treating time. In microhardness test, it found that more temperature and treating time cause more hardness. Finally the resistivity was decreased in steps with temperature and treating time. It can be concluded that these variables may increase the graphitizing degree, and minimizing in interplanar distance for samples comparing with ideal one, when these variables may increased.